Can high-intensity interval training improve health outcomes among people with substance use disorders?: a systematic review and preliminary meta-analysis - Türkmen, Cagdas; Martland, Rebecca; Grilli, Maurizio; Stubbs, Brendon; Roessler, Kirsten K.; Hallgren, Mats (Mental health and physical activity, 2024)
Background and aim - Substance use disorders (SUDs) are marked by high relapse rates and comorbid somatic and mental health issues. High-intensity interval training (HIIT), a time-efficient form of exercise, may offer potential benefits in addressing these issues. The aim of this systematic review and preliminary meta-analysis was to evaluate the health benefits, safety and adherence of HIIT interventions in individuals with SUDs. - Methods - Systematic searches were conducted in PubMed, Embase, Cochrane Library, Web of Science Core Collection, PsycINFO, ClinicalTrials.gov and the ICTRP for intervention studies published from inception until March 12, 2024. Study quality was assessed using the EPHPP tool. Preliminary meta-analyses were conducted if ≥ 3 studies reported data on the outcomes of interest. To compare the HIIT and control groups, mean differences (MDs) were calculated as effect sizes for outcomes measured on the same scale, while Hedges’ g was used for outcomes measured on different scales. - Results - Six intervention studies (N = 327 at baseline; 99% men) were included, comprising one non-randomised and five randomised controlled trials. Preliminary meta-analyses indicated a moderate increase in VO2max after 2-4 months (3 studies; MD = 2.06 ml/kg/min, 95% CI = 1.02 to 3.09, p < 0.001) and a modest reduction in drug craving after 3 weeks to 6 months (3 studies; Hedges’ g = -0.31, 95% CI = -0.59 to -0.03, p < 0.05) in the HIIT groups, compared to control groups. No evidence for heterogeneity among the included trials was found. Data on other outcomes were insufficient or inconsistent, limiting interpretability. The included trials were rated as being of low to moderate quality. - Conclusion - HIIT may improve cardiorespiratory fitness and reduce drug craving among individuals with SUDs, potentially improving treatment outcomes and lowering the risk of relapse. Further research is needed to assess its impact on other outcomes (e.g., cognitive functioning and mental health), and to compare its effectiveness with other forms of exercise. Supported HIIT interventions are shown to be feasible and safe among inpatients, but studies involving outpatients and non-treatment seekers are also needed.